Microwave dielectric properties of (1-x)Ba(Mg1/3Ta2/3) O3 – (x)Ba(Mg1/8Ta3/4)O3 ceramics synthesized by one pot metathesis process. Issue 1 (3rd April 2020) - Bisht, Yogita; Abhilash, Pullanchiyodan; Lekshmi, Deepa Rajendran; Thirumal, M.
Abstract: Complex perovskites (1-x)Ba(Mg1/3 Ta2/3 )O3 – (x)Ba(Mg1/8 Ta3/4 )O3 (0 ≤ x ≤ 1) were investigated for possible solid solution and composite range using one pot metathesis process. This process lowers the synthesis temperature of Ba-Mg-Ta ceramics to just 1100 °C. Till x = 0.5 the powder X-ray pattern shows the presence of only Ba(Mg1/3 Ta2/3 )O3 phase. Above x = 0.5 both Ba(Mg1/3 Ta2/3 )O3 and Ba(Mg1/8 Ta3/4 )O3 phase starts crystallizing. The samples can be sintered to >90% density at around 1350 °C. Dielectric properties measured at GHz frequency exhibits values in the range: εr = 22 − 29, Q.f = 7000 − 36000 GHz and τf = 14 − 50 ppm/ °C.